Physicochemical modifications in microwave-irradiated chitosan: biopharmaceutical and medical applications - Elsayed Mahmoud, Doaa; Billa, Nashiru (Journal of biomaterials science. Polymer ed., 2024)
Biopharmaceutical and biomedical applications of chitosan has evolved exponentially in the past decade, owing to its unique physicochemical properties. However, further applications can be garnered from modified chitosan, specifically, depolymerized chitosan, with potentially useful applications in drug delivery or biomedicine. The use of microwave irradiation in depolymerization of chitosan appears to be more consequential than other methods, and results in modification of key physicochemical properties of chitosan, including molecular weight, viscosity and degree of deacetylation. In-depth review of such microwave-depolymerized chitosan and subsequent potential biopharmaceutical or biomedical applications has not been presented before. Herein, we present a detailed review of key physicochemical changes in chitosan following various depolymerization approaches, with focus on microwave irradiation and how these changes impact relevant biopharmaceutical or biomedical applications.